Dose dependent cerebellar atrophy in glioma patients after radio (chemo)therapy - Raschke, Felix; Seidlitz, Annekatrin; Wesemann, Tim; Löck, Steffen; Jentsch, Christina; Platzek, Ivan; Petr, Jan; Hoff, Jörg van den; Kotzerke, Jörg; Beuthien-Baumann, Bettina; Baumann, Michael; Linn, Jennifer; et al. (Radiotherapy and oncology, 2020)
Background and purpose: Radiotherapy is a standard treatment option for high-grade gliomas. Brain atrophy has previously been associated with radiotherapy. The goal of this study was to investigate dose dependent cerebellar atrophy using prospective, longitudinal MR data from adult glioma patients who received radiotherapy. Materials and methods: Cerebellar volumes were measured using T1-weighted MR images from 91 glioma patients before radiotherapy (N = 91) and from longitudinal follow-ups acquired in three monthly intervals (N = 349). Relative cerebellar volumes were calculated as ratios to the corresponding baseline values. Univariate mixed effects models were used to determine factors that were significantly associated with relative cerebellar volumes. These factors were subsequently included as fixed effects in a final multivariate linear mixed effects model. Results: In multivariate analysis, cerebellar volume decreased significantly as a function of time (p < 0.001), time x dose (p < 0.001) and patient age (p = 0.007). Considering a 55 year patient receiving a mean cerebellar dose of 0 Gy (10 Gy), the linear mixed effects model predicts a relative cerebellar volume loss of 0.4% (2.0%) after 1 year and 0.7% (3.6%) after 2 years. Compared to patients treated with photons, the cerebellar dose was significantly lower in patients treated with proton therapy (p < 0.001, r = 0.62). Conclusion: Cerebellar volume decreased significantly and irreversibly after radiotherapy as function of time and mean cerebellar dose. Further work is now needed to correlate these results with cognitive function and motor performance. (C) 2020 Elsevier B.V. All rights reserved.
Gesehen am 11.12.2020